Is climate change responsible for changing landslide activity in high mountains? - Huggel, Christian; Clague, John J; Korup, Oliver (Wiley-Blackwell Publishing, Inc., 2012)
Climate change, manifested by an increase in mean, minimum, and maximum temperatures and by more intense rainstorms, is becoming more evident in many regions. An important consequence of these changes may be an increase in landslides in high mountains. More research, however, is necessary to detect changes in landslide magnitude and frequency related to contemporary climate, particularly in alpine regions hosting glaciers, permafrost, and snow. These regions not only are sensitive to changes in both temperature and precipitation, but are also areas in which landslides are ubiquitous even under a stable climate. We analyze a series of catastrophic slope failures that occurred in the mountains of Europe, the Americas, and the Caucasus since the end of the 1990s. We distinguish between rock and ice avalanches, debris flows from de-glaciated areas, and landslides that involve dynamic interactions with glacial and river processes. Analysis of these events indicates several important controls on slope stability in high mountains, including: the non-linear response of firn and ice to warming; three-dimensional warming of subsurface bedrock and its relation to site geology; de-glaciation accompanied by exposure of new sediment; and combined short-term effects of precipitation and temperature. Based on several case studies, we propose that the following mechanisms can significantly alter landslide magnitude and frequency, and thus hazard, under warming conditions: (1) positive feedbacks acting on mass movement processes that after an initial climatic stimulus may evolve independently of climate change; (2) threshold behavior and tipping points in geomorphic systems; (3) storage of sediment and ice involving important lag-time effects.